Educação popular e extensão rural: o caráter pedagógico das ações de ATER no Perímetro Irrigado Público Federal Baixo Acaraú - Costa, Rita de Cassia Marques (2009)
This investigation aim studying the relation between popular education and actions of Technique Assistance and Rural Extension – TARE to Federal Public Irrigate Perimeter at Baixo Acaraú, due to its importance as political instrument of state TARE. The rural extension seek for maintainable development of the communities through educative process to contribute and incorporate changes at methods, procedures and organization techniques of the productive process organization, in function of larger productivity and improvement of life quality of the rural population. This current demand of rural extension requires to the professional the increase of new practice, technical knowledge at the range of academic formation and abilities to recover and valorize the knowledge of the farmers. This way, appears lots of visions related to TARE practices at this irrigate perimeter as attempt to search for answers to the question: What is the pedagogic character of TARE actions to the development of Public Irrigate Perimeter at Baixo Acaraú? To study the TARE actions at that Public Irrigate Perimeter and to know its pedagogic character seeking the repercussion at local community daily, contributing to TARE public policy, was the target of this study. The research was descriptive and explanatory, appealing to a qualitative approach, having as draw “the case study”. Maintainable development, rural extension and popular education were presented as theoretical reference. The conclusion of this study point to the necessity of a redirection at the academic formation of professionals inserted at TARE actions, such as the improvement of public policy to assure rural extension service and the inclusion of professionals with pedagogical formation to develop evaluation actions, planning and supervising the actions of the extensionists.